Badania nad lubuską tożsamością z perspektywy historyka = Research into Lubusz identity from a historian`s perspective - Nodzyński, Tomasz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The starting point of the investigation is the question of the sources of identity of the region which was created for political reasons in 1945. The questions that follow pertain to the motives, objectives, and results of research conducted by organisations and institutions such as Polskie Towarzystwo Historyczne [the Polish Historical Society] (since 1954), Lubuskie Towarzystwo Kultury [the Lubuskie Society for Culture] (1957-1992), Lubuskie Towarzystwo Naukowe [the Lubuskie Scientific Society] (since 1964), Gorzowskie Towarzystwo Naukowe [the Gorzow Scientific Society] (1978-2018), Gorzowskie Towarzystwo Społeczno-Kulturalne [the Gorzow Social and Cultural Society] (1970-1983) Gorzowskie Towarzystwo Kultury [the Gorzow Society for Culture] (1975-2003) the Higher School of Pedagogy - University of Zielona Gora (since 1971), the State Higher Vocational School - The Jacob of Paradies University in Gorzow Wielkopolski (since 1998), Collegium Polonicum in Słubice (since 1998), as well as archives, museums, public libraries, and social organisations in Zielona Gora, Gorzow Wielkopolski, and other towns and cities in the present Lubuskie Voivodeship. The author attempts to demonstrate the socio-political context in which the results of this research were published, both before and after 1989, and to outline their future prospects.
Keywords: historia; badania; tożsamość; Ziemia Lubuska; history; researches; identity; Lubuskie Region